Synthesis of Functionalized Multi-wall Carbon Nanotubes/polyaniline Composite by Physical Mixing and Evaluation of its Thermoelectric Performance - Khan, Waseem; K. Chaudhury, Partap; M. Siddiqui, Azher; Saini, Parveen (Current Nanomaterials, 2016)
Background: The impending energy crisis and increasing environmental pollution have prompted researchers to look for new functional materials to efficiently address these issues. In this context the useful properties of thermoelectric materials can be harvested to tackle the aforementioned issues. Based on the synergistic interplay of properties of carbon nanotubes and conducting polymers (in particular polyaniline) their nanocomposite can be utilized efficiently to replace the conventional inorganic thermoelectric materials. Method: Multiwall carbon nanotubes (CNTs) were subjected to acid refluxing to form functionalized CNTs (FCNTs) with carboxylic functionality and improved dispersibility in solvents. Subsequently, FCNTs filled polyaniline (PANI) matrix based composite (PFCNT) is formed and its thermoelectric (TE) performance is evaluated. Results: The electron microscopy images provide the visual evidence of dispersion of FCNTs inside PANI matrix and formation of heterojunctions. The FCNT composite displays optimum electrical conductivity & Seebeck coefficient which in combination with low thermal conductivity facilitates the realization of moderate yet promising value of TE figure of merit (i.e. ZT value) reaching 0.001 at room temperature. Conclusion: We have successfully functionalized CNTs (FCNTs) and synthesized FCNTs/PANI composites (PFCNT) by wet phase physical mixing of the phases. The heterostructure formation between FCNTs and PANI enables the PFCNT composite to exhibit a promising value of TE figure of merit (ZT 0.001) at room temperature.
Keywords: seebeck coefficient